Telecom Regulators : Converging Trends? - Kerf, Michel; Schiffler, Manuel; Torres, Clemencia (World Bank, Washington, DC, 2012)
Officials in developing countries with legal and political systems of continental European origin often argue that the model of independent regulatory agencies for utilities is appropriate only for Anglo-Saxon countries. Yet countries in continental Europe have also adopted this model. Comparing the telecommunications regulatory agencies in the United Kingdom, the United States, France, Germany, and Spain, this Note finds divergence in some respects but striking convergence in overall approach. This approach might not be right for all developing countries, but it cannot be rejected on the grounds that it works in Anglo-Saxon countries only.